An Agent-Based Model of Leader Emergence and Leadership Perception within a Collective. (28th April 2020) - Cao, Shun; MacLaren, Neil G.; Cao, Yiding; Dong, Yingjun; Sayama, Hiroki; Yammarino, Francis J.; Dionne, Shelley D.; Mumford, Michael D.; Connelly, Shane; Martin, Robert; Standish, Colleen J.; Newbold, Tanner R.; et al.
Abstract : Effective teamwork in an initially leaderless group requires a high level of collective leadership emerging from dynamic interactions among group members. Leader emergence is a crucial topic in collective leadership, yet it is challenging to investigate as the problem context is typically highly complex and dynamic. Here, we explore leadership emergence and leadership perception by means of computational simulations whose assumptions and parameters were informed by empirical research and human-subject experiments. Our agent-based model describes the process of group planning. Each agent is assigned with three key attributes: talkativeness, intelligence, and credibility . An agent can propose a suggestion to modify the group plan as a speaker or respond and evaluate others' suggestions and leadership as a listener. Simulation results suggested that agents with high values of talkativeness, intelligence, and credibility tended to be perceived as leaders by their peers. Results also showed that talkativeness may be the most significant and instantaneous predictor for leader emergence of the three investigated attributes: talkativeness, intelligence, and credibility. In terms of group performance, smaller groups may outperform larger groups regarding their problem-solving ability in the beginning, but their performance tends to be of no significant difference in a long run. These results match the empirical literature and offer a mechanistic, operationalized description of the collective leadership processes.